ANALYSIS OF THE INFLUENCE OF ASSET QUALITY, LIQUIDITY, AND CAPITAL ON PROFITABILITY - Addys Aldizar; Vepy Agustina (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study is to analyze whether there is an effect of Asset Quality, Liquidity, and Capital on Profitability. Objects taken for this research are Islamic Commercial Banks whose financial reports can be accessed and viewed by each official website of Islamic banks registered with the Financial Services Authority (OJK) for the period 2015 to 2019. This study uses 6 Islamic commercial banks with sample selection using purposive sampling method. The results of this study indicate that Asset Quality has a negative regression coefficient and a significant value smaller than alpha, so it can be said that Asset Quality has a significant effect on profitability. Meanwhile, liquidity has a negative regression coefficient with a significant value greater than alpha, so it can be said that liquidity has no significant effect on profitability. Keywords: Non Performing Financing, Financing To Deposit Ratio, Capital Adequacy Ratio, Return On Assets.